2018
DOI: 10.1002/job.2337
|View full text |Cite
|
Sign up to set email alerts
|

Two facets of conscientiousness and the knowledge sharing dilemmas in the workplace: Contrasting moderating functions of supervisor support and coworker support

Abstract: Summary This study adopts self‐ and other‐centered approaches to explain how the two facets of conscientiousness (i.e., dutifulness and achievement striving) distinctly resolve knowledge sharing dilemmas among employees. It also explores how the critical social surroundings of employees (i.e., supervisor support and coworker support) neutralize or activate the effects of dutifulness and achievement striving on knowledge‐sharing behavior. Our analysis of the data collected from 150 employee–supervisor dyads cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 63 publications
(163 reference statements)
4
62
0
Order By: Relevance
“…Several studies have found that an individual's personality may influence the implementation of the knowledge sharing process (Lee et al, 2015). We focus on the characteristics of conscientiousness because conscientiousness affects the moral dilemma of knowledge sharing (Chae et al, 2019). Specifically, conscientiousness comprises two separate and primary dimensions of dutifulness and achievement-striving, with each having varying influences on individual behaviors (Moon, 2001;Dudley et al, 2006;Chae et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have found that an individual's personality may influence the implementation of the knowledge sharing process (Lee et al, 2015). We focus on the characteristics of conscientiousness because conscientiousness affects the moral dilemma of knowledge sharing (Chae et al, 2019). Specifically, conscientiousness comprises two separate and primary dimensions of dutifulness and achievement-striving, with each having varying influences on individual behaviors (Moon, 2001;Dudley et al, 2006;Chae et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…To date, an examination of the moderating influence of the two facets of conscientiousness is still lacking, and previous studies have mainly regarded conscientiousness as a monolithic construct. Few studies considered the opposing implications of two distinct personality dimensions of conscientiousness (Chae et al, 2019). Therefore, the current study focuses on investigating the moderating effects of dutifulness and achievement-striving in relation to prosocial motivation and knowledge sharing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, the extent to which one is the recipient of shared knowledge is related to personal levels of job performance (Wu, Yeh, & Hung, ). The relevance of knowledge sharing as a prosocial coping response is also highlighted by Chae et al (), who examined 150 employer–supervisor dyads and found that dutifulness (an other‐centered construct) was positively associated with knowledge sharing, whereas achievement striving (a self‐centered construct) was not.…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 79%
“…The majority of studies on knowledge sharing have focused on its antecedents. Findings indicate that the primary determinants of an individuals' propensity to share knowledge are commitment, OCBs, perceived trust, and interpersonal support (see Chae, Park, & Choi, ; Han, Seo, Yoon, & Yoon, ; Lee, Kim, & Yun, ; Lee, Yoo, & Yun, ; Lin & Hsiao, ; Nerstad et al, ; Zhao, Liu, Li, & Yu, in press).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%